Administrative Contract: Its Definition, Distinguishing Criteria, and Types According to the Administrative Contracts Regulations and Judicial Rulings (Journal of human and social sciences, 2023)
Administrative contracts are among the most important legal instruments used by public authorities to achieve their objectives in providing public services and promoting the public interest. These contracts are characterized by a special legal nature that distinguishes them from civil contracts, granting the administration unusual powers to modify contract terms, supervise execution, impose penalties, or terminate the contract to serve the public good. The study focuses on three main areas: the definition of administrative contracts, the criteria distinguishing them, and their main types according to the Administrative Contracts Regulations and Libyan judicial rulings. It identifies three essential elements of an administrative contract: one party must be a public legal entity, the contract must relate to a public service, and it must include exceptional clauses not commonly found in civil contracts. The study also reviews the main types of administrative contracts in Libya, including public works contracts, supply contracts, and concession contracts, highlighting their role in facilitating administrative operations and achieving general development in accordance with administrative law. Keywords: Administrative contract, Administrative law, Public service, Exceptional clauses, Libya.
Keywords: Administrative Contract; Administrative Law; Public Service; Exceptional Clauses; Libyan Judiciary